2018
DOI: 10.2147/imcrj.s171645
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous renal artery dissection associated with sexual intercourse: a case report

Abstract: Spontaneous renal artery dissection is a rare cause of renal infarction and can be a diagnostic challenge at times, necessitating high index of suspicion. Other common underlying causes, especially thromboembolic phenomena, need to be considered and investigated first before making this uncommon diagnosis with vascular imaging studies. Very few cases did report strenuous exercise as a predisposing factor for the development of spontaneous renal artery dissection, but we believe that sexual intercourse has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For obvious reasons, sexual intercourse may be an underreported trigger, as the case discussed here suggests. Interestingly, it was the second one observed by the corresponding author (Supplementary Case S1, Supplementary Figures S2–S4), and another case was recently published 7 …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…For obvious reasons, sexual intercourse may be an underreported trigger, as the case discussed here suggests. Interestingly, it was the second one observed by the corresponding author (Supplementary Case S1, Supplementary Figures S2–S4), and another case was recently published 7 …”
Section: Discussionmentioning
confidence: 74%
“…The case reported here highlights this emerging diagnosis as a cause of kidney infarction and suggests that it should be considered in the case of symptoms that appear suddenly after physically strenuous activities or sexual intercourse 6, 7…”
Section: Introductionmentioning
confidence: 80%
“…Adverse development of the media and alterations of the vasa vasorum, severe atherosclerosis, and blood flow shear stress may be pathogeny. Malignant hypertension, fibromuscular dysplasia (15), strenuous exercise (including sexual) (17), taking medication (18,19), Marfan syndrome (20), and Ehlers-Danlos syndromes ( 4) are all possible risk factors. In our two case studies, we found that both of the patients had a long history of smoking, which was similar to the reports by other researchers (6,11,21).…”
Section: Discussionmentioning
confidence: 99%